2019
DOI: 10.1002/cncr.32147
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and cost‐effectiveness of patient navigation programs across the cancer continuum: A systematic review

Abstract: Published studies regarding patient navigation (PN) and cancer were reviewed to assess quality, determine gaps, and identify avenues for future research. The PubMed and EMBASE databases were searched for studies investigating the efficacy and cost‐effectiveness of PN across the cancer continuum. Each included article was scored independently by 2 separate reviewers with the Quality Assessment Tool for Quantitative Studies. The current review identified 113 published articles that assessed PN and cancer care, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
179
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(186 citation statements)
references
References 134 publications
(420 reference statements)
2
179
0
5
Order By: Relevance
“…As such, limited historical data and a lack of a control group make it difficult to definitely and quantitatively assess the program's impact on breast cancer outcomes. However, this program clearly demonstrates the utility in implementing evidence‐based approaches that have been shown to increase breast cancer screening compliance and reduce barriers …”
Section: Discussionmentioning
confidence: 99%
“…As such, limited historical data and a lack of a control group make it difficult to definitely and quantitatively assess the program's impact on breast cancer outcomes. However, this program clearly demonstrates the utility in implementing evidence‐based approaches that have been shown to increase breast cancer screening compliance and reduce barriers …”
Section: Discussionmentioning
confidence: 99%
“…We believe that the coordination of a patient's PrEP care would be more efficient, organized, and reduce cost when involving a panel management strategy such as PrEP-OI versus solely reliant on healthcare providers. Although we did not have a cost-effectiveness component for this study, studies of patient navigation-type services for other conditions have found them to be cost-effective [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have assessed the use of Patient Navigation in Latina BCS; it has successfully been used to reduce time to diagnosis and treatment, and increase informed decision‐making regarding clinical trial participation 29‐31 . However, studies have had conflicting results, and several studies have been hindered by methodological shortcomings like lack of robust evaluation strategies, control groups, adequate descriptions of promotoras , long‐term follow‐up assessments, or large, diverse samples 32,33 . In addition, few studies have focused on patient QoL or satisfaction with care 34‐36 .…”
Section: Introductionmentioning
confidence: 99%